Preliminary evaluation of secondary Musa polyploids at IITA breeding station - Ortíz, R.; Vuylsteke, D.R. (1994)
Secondary triploids were produced by crossing primary tetraploids with selected diploid partners and the parthenocarpic banana (Galeo). Comparisons between secondary tetraploids and secondary triploids showed that the secondary tetraploids generally had lower yields than secondary triploids. The percentage of clones selected was also higher in the secondary triploids than for secondary tetraploids, which demonstrates the more efficient breeding potential of the former. Nevertheless some resistant secondary tetraploids were selected for further testing due to their acceptable bunch weights and/or short plant height in the plant crop. The highest yielding secondary triploid was obtained by crossing IITA's primary tetraploid plantain 'TMPx 4479-1' ('Bobby Tannap' x 'Calcutta 4') with the improved diploid banana 'SH-3362' from the Fundación Hondureña de Investigación Agrícola (FHIA). Nonadditive genetic effects may control heterosis for bunch weight in Musa.